Developing a Game-Assisted Focus Group Discussion Activities Model for Javanese Literacy Learning of LIS Students - Andriyana Fatmawati; Thoriq Tri Prabowo; Nini Salwa Istiqamah (Prodi Pendidikan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2026)
Javanese script literacy competence is essential for managing Javanese script; however, students’ ability to read Javanese script remains relatively low. This study focuses on developing and validating a learning model based on students' needs in the Library and Information Science Program. This study employs the Sugiyono Research and Development method, which comprises five stages: analysis of potential and problems, data collection, product design, design validation, and design revision. The results of the needs analysis indicate that students require an innovative, engaging, and technology-supported learning method to overcome difficulties in understanding the complex structure of Javanese script. The GAFOD model integrates focus group discussions with educational games based on digital technology. Validation results from three experts yielded an average score of 93.4%, placing it in the “very good” category and indicating suitability for implementation without revision. The GAFOD stages include pre-activity (determining facilitators, participants, time, and guidelines), implementation (introduction, presentation of material, FGD, and reading practice through games), and post-activity, includes analysis of discussion results, evaluation, and reflection. The GAFOD model for Javanese script learning was successfully developed with structured stages for prospective librarians. This model contributes to the pedagogical innovation in higher education and the sustainable preservation of cultural heritage.